Self-healing graphene oxide-based composite for electromagnetic interference shielding. (December 2019) - Sim, Hyeon Jun; Lee, Duck Weon; Kim, Hyunsoo; Jang, Yongwoo; Spinks, Geoffrey M.; Gambhir, Sanjeev; Officer, David L.; Wallace, Gordon G.; Kim, Seon Jeong
Abstract: The electromagnetic pollution issues have been arising from the fast-growing development for electronic devices. Hence, the demand for materials with high electromagnetic interference (EMI) shielding performance has increased. Here, we developed self-healable, flexible and printable graphene oxide/silver nanowire films and textiles with excellent EMI shielding performance. The maximum electromagnetic interference shielding effectiveness (EMI SE) of 92 dB was recorded for an 18 μm-thickness film. In addition, the specific EMI shielding effectiveness was 31 dB cm3/g or 48, 275 dB cm2/g when normalized to film thickness. Both values are higher than reported EMI shielding products. The composite film and coated textile were tolerant of damage induced by cracking or scratching. Damaging the films by cracking reduced the electrical conductivity, mechanical properties, and the EMI SE was decreased from 72 dB to 56 dB at 8.2 GHz. After the healing process, the EMI SE was recovered to 71 dB and mechanical properties restored. The EMI SE of textile reached a maximum of 30 dB which is suitable to use as a commercial EMI shielding product. In addition, the textile exhibited high flexibility, and showed excellent mechanical stability with no change in performance after 1000 bending cycles. Graphical abstract: Image 1